Perancangan Informasi Terdokumentasi Untuk Monitoring Pada Proses Pengadaan Bahan Baku Sesuai Dengan Persyaratan Iso 9001:2015 Menggunakan Pendekatan Business Process Management - Fauzan, Mochamad Badar; Sutari, Wiyono; Hakim, Bela Pitria (Innovative: Journal Of Social Science Research, 2024)
The raw material procurement process plays an important role in ensuring production quality at CV XYZ. To support the smooth procurement process according to the company's plan, a procedure or system is needed that refers to certain standards, such as ISO 9001:2015, to document every piece of information in its activities. The lack of an information documentation system that complies with ISO 9001:2015 causes various errors in the procurement process, such as inconsistencies in the type, color, and quantity of raw materials. This study aims to design a documented information system for monitoring the raw material procurement process in accordance with ISO 9001:2015 requirements. The method used is Business Process Management, with limitations up to the process re-design stage. The design stages in this study include process identification, process discovery, process analysis, and process re-design. The results of the study are in the form of a documented information system in the form of a dashboard and digital documents from each procurement process activity, designed in accordance with ISO 9001:2015 requirements and related clauses. This design is also adjusted to the needs of documenting information in each procurement process activity in the company.